Contributing Factors of Mental Stress among Parents of Thalassemia-Affected Children - Rayhan, Md Golam; Farha, Tamsasul; Soma, Adrika Roy; Purni, Sharif Nur Hafiza; Khan, Mohammad Zahirul Islam; Nurunnabi, Mohammad (Community Based Medical Journal, 2025)
Thalassemia is a chronic genetic disorder requiring lifelong treatment, which creates significant emotional and financial burdens for families. A cross-sectional study was conducted in the Departments of Hemato-oncology of Dhaka Shishu Hospital and Bangladesh Thalassemia Hospital, Dhaka, Bangladesh, from January to December of 2018, to identify the factors contributing to mental stress among parents of thalassemia-affected children. Data were collected using a pretested semi-structured questionnaire and the 'Parental Stress Scale' (PSS) to assess stress levels. 56.7% of the parents were female, with 63.8% being 40 years or younger. A majority of parents (61.7%) lived in rural areas, and 68.1% had a monthly family income of ≤20,000 BDT. Regarding the children’s condition, 86.5% had one child with thalassemia, and 70.9% of parents could afford the treatment costs. The study also revealed that 77.3% of children required blood transfusions less than 30 days apart, and 54.6% required at least 12 transfusions per year. The average monthly drug and treatment costs were significant financial burdens on the parents. The mean PSS score was 58.2±4.6, with more than half of the parents (53.2%) experiencing high stress levels. The study found significant associations between PSS scores and factors such as the number of blood transfusions required, treatment assistance from others, and the reluctance to attend social events with affected children. This study highlights the substantial mental and financial stress faced by parents caring for children with thalassemia, underlining the need for targeted interventions to support these families. CBMJ 2025 July: vol. 14 no. 02 P:126-133